Sorting and wage premiums in immoral work - Florian Schneider; Fanny Brun; Roberto A. Weber (University of Zurich, Department of Economics, 2024)
We use surveys, laboratory experiments and administrative data to study how heterogeneity in the perceived immorality of work and in workers' aversion to acting immorally impact labor market outcomes. Immoral work is associated with higher wages, both in administrative data and in causal experimental evidence. Individuals more willing to engage in immoral conduct find employment in firms and industries perceived as immoral less aversive and have higher employment rates in immoral work in the laboratory. These phenomena appear to be driven by impure social motives, reflecting a desire not to be involved with immoral work, rather than by consequentialist concerns.
Keywords: C92; J31; D03; 330; Wage premium; immoral behavior; impure social preferences; sorting; experiments